E-NETWORKING OF ALL INDIA COORDINATED RESEARCH PROJECT ON TUBER CROPS - Mithra, Santhosh; George, James; C.S, Abhinand; Sreekumar, J (JOURNAL OF ROOT CROPS, 2015)
All India Coordinated Research Project on Tuber Crops is networked through the medium of internet. The website http://www.aicrptc.in was developed for this purpose. Front end of the site was developed using PHP and the back end in MySQL. The database contains 35 tables to store, retrieve and update various data relating to the AICRPTC as well as that of this website. Users of this site are the project coordinator, centres and public. Each user is assigned separate rights on the data. Project coordinator is given all the administrative privileges. Through this site the centres can communicate between themselves as well as with the Head Quarters. They can send messages, reports and data through this facility and can do chatting also. Details of the projects, job schedule, budget, staff position etc. can be updated from time to time through this medium. Details of the planting material availability of the centres are displayed to the public through this site. Anybody can send request for planting materials through this site. Data entry of the projects also can be done through this website.